Pengaruh Pembelajaran Berdiferensiasi terhadap Kemampuan Berpikir Kritis Matematis Mahasiswa Pendidikan Matematika di Perguruan Tinggi - Pratiwi Pujilestari Alam; Rustiani S; Hafsyah (Lembaga Bale Literasi, 2026)
This study aims to examine the effect of differentiated instruction on the mathematical critical thinking ability of undergraduate students in the Mathematics Education Program at Universitas Muhammadiyah Enrekang. The study is motivated by the demands of 21st-century education, which emphasize the development of higher-order thinking skills, particularly critical thinking in mathematics learning. A pre-experimental method with a one-group pretest–posttest design was employed. The participants were selected using purposive sampling. Data were collected through a mathematical critical thinking test based on indicators of analysis, evaluation, inference, and reasoning. The results indicate a significant improvement in students’ mathematical critical thinking ability after the implementation of differentiated instruction. This approach enables the adaptation of content, process, and product according to students’ needs, thereby enhancing cognitive engagement and conceptual understanding. In conclusion, differentiated instruction has a positive effect on students’ mathematical critical thinking ability. This study contributes to the development of adaptive and inclusive learning strategies in higher education